Antioxidant Activity Test of (Acalypha indica L) Extract - Nursafitri, Nursafitri; Santoso, Tri (Universitas Tadulako, 2023)
The antioxidant activity test of Acalypha indica L has been carried out. This study aimed to determine the IC50 value of the Acalypha indica L extract. The radical concentration of 2,2-diphenyl-1-picrylhydrazyl (DPPH) after adding Acalypha indica L extract was determined using a UV-Vis spectrophotometer. The concentration variations used in Acalypha indica L extract were 15.48 ppm, 30.96 ppm, 46.44 ppm, and 61.92 ppm. The results showed that the IC50 value of Acalypha indica L extract was 41,259 ppm, while the IC50 value of vitamin C as a comparison was 50.626 ppm. Based on the IC50 value data above, it can be seen that the antioxidant of Acalypha indica L extract is robust compared to vitamin C.